Controle interno na administração pública: estudo na Universidade Federal do Ceará (UFC) - Soares, Larissa Fidélis (2022)
Internal control is an integrated process, structured in the form of a system, which permeates all organizational levels and involves all the people who are part of an entity. The way these are structured, formalized and perceived differs, however, according to the particularities of each institution. Nevertheless, the need to structure and evaluate internal controls leads to the adoption of reference models such as COSO. This study aimed to analyze aspects of the internal control system of the Pró-Reitoria (Pro-Rectory) of Planning and Administration of the Universidade Federal do Ceará (Federal University of Ceará) from the perspective of the components of the COSO model. The research is characterized as descriptive, a single case study, with a quantitative approach in the analysis of primary data, collected by applying a questionnaire to PROPLAD servers to analyze their perception of the internal controls existing in the Pro-Rectory. The COSO 2013 framework was chosen as a parameter, due to presenting a widely recognized internal control structure. From the analysis of the results, it was identified that the monitoring activities indicate a degree of total similarity to COSO 2013. As for the risk assessment, it shows total distance from the framework. The components environment control, control activities and information and communication present similarity rates of 85.71%, 50% and 60%, respectively. The general analysis of the internal controls of the Pro-Rectory, encompassing all components, points out that PROPLAD's internal control system is 58.33% similar to COSO 2013, according to respondents. The results obtained also indicate that the civil servants who hold a management position or a gratified role perceive the characteristics of internal control components to a greater degree than civil servants that do not. It is concluded that PROPLAD’s internal controls are partially in line with the components of the COSO 2013 model and that the perception of the respondents becomes more acute due to the exercise of a management position or a gratified role.